2008
DOI: 10.1155/2008/581348
|View full text |Cite
|
Sign up to set email alerts
|

Improved Insulin Resistance and Lipid Metabolism by Cinnamon Extract through Activation of Peroxisome Proliferator‐Activated Receptors

Abstract: Peroxisome proliferator-activated receptors (PPARs) are transcriptional factors involved in the regulation of insulin resistance and adipogenesis. Cinnamon, a widely used spice in food preparation and traditional antidiabetic remedy, is found to activate PPARγ and α, resulting in improved insulin resistance, reduced fasted glucose, FFA, LDL-c, and AST levels in high-caloric diet-induced obesity (DIO) and db/db mice in its water extract form. In vitro studies demonstrate that cinnamon increases the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(141 citation statements)
references
References 25 publications
5
134
0
2
Order By: Relevance
“…4 PPARs are ligand-activated nuclear hormone receptors expressed mainly in brown adipose tissue and the liver. Activation of various isoforms lowers levels of plasma triglycerides, elevates levels of HDL-C, and increases insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 PPARs are ligand-activated nuclear hormone receptors expressed mainly in brown adipose tissue and the liver. Activation of various isoforms lowers levels of plasma triglycerides, elevates levels of HDL-C, and increases insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…4 In animal studies, aqueous cinnamon extracts have been shown to increase the expression of peroxisome proliferator-activated receptors (PPARs), which are transcriptional factors involved in the regulation of insulin resistance and adipogenesis, resulting in improved lipid and glucose metabolism. 5 Several randomized controlled trials (RCTs) in humans have been conducted to explore cinnamon's efficacy; however, they report conflicting results.…”
Section: Cinna M On Use In T Y Pe 2 Dia Be T Esmentioning
confidence: 99%
“…Moreover, cinnamon bark proanthocyanidins prevents the formation of advanced glycation end-products [13]. Cinnamon extract also improves insulin resistance and lipid metabolism by activating peroxisome proliferator-activated receptors (PPARs) [14], and stimulates insulin secretion in pancreatic β-cell line [15]. Nevertheless, there has been no recent literature to evaluate the intestinal α-glucosidase and pancreatic α-amylase inhibitory activities of various cinnamon bark species.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of interaction between the components of dietary supplements and oral anti-diabetic agents have not been explicitly described in the literature. The possible mechanisms of hypoglycemic action have been summarized for many dietary supplements, which makes it possible to hypothesize that drug-dietary supplement interaction may indeed occur [11][12][13][14]. In this study, almost half the T2DM patients took dietary supplements, which could indicate a high potential risk of interactions with drugs or nutrients.…”
Section: Discussionmentioning
confidence: 84%